2013
DOI: 10.1038/ncomms3497
|View full text |Cite
|
Sign up to set email alerts
|

Functional lacrimal gland regeneration by transplantation of a bioengineered organ germ

Abstract: The lacrimal gland has a multifaceted role in maintaining a homeostatic microenvironment for a healthy ocular surface via tear secretion. Dry-eye disease, which is caused by lacrimal gland dysfunction, is one of the most prevalent eye diseases that cause corneal epithelial damage and results in significant loss of vision and a reduction in the quality of life. Here we demonstrate orthotopic transplantation of bioengineered lacrimal gland germs into adult mice with an extra-orbital lacrimal gland defect, a mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(116 citation statements)
references
References 51 publications
3
112
0
1
Order By: Relevance
“…Thus, bioengineered salivary and lacrimal gland germs could be reconstituted by the organ germ method. 58,59 We confirmed that the bioengineered salivary and lacrimal glands could develop into mature glands though their transplantation into an adult mouse (Fig. 5B).…”
Section: Functional Salivary Gland and Lacrimal Gland Regenerationsupporting
confidence: 86%
“…Thus, bioengineered salivary and lacrimal gland germs could be reconstituted by the organ germ method. 58,59 We confirmed that the bioengineered salivary and lacrimal glands could develop into mature glands though their transplantation into an adult mouse (Fig. 5B).…”
Section: Functional Salivary Gland and Lacrimal Gland Regenerationsupporting
confidence: 86%
“…Recent progress has been made in the development of strategies for regeneration and engineering of a variety of tissues, including skin (79,92), corneal epithelium (43), cartilage (85), bone (10,11), bladder (77), and lacrimal (48) and salivary glands (83). Determining the capacity of dispersed cells or tissue fragments to reassemble into native structures and the underlying mechanisms involved should provide novel insights to improve tissue regeneration approaches.…”
Section: Discussionmentioning
confidence: 99%
“…(B) Then, submandibular gland (3) was noted at just inferolateral side of the ear. W e observed that the lacrimal gland (1) and parotid gland (2) were in front of the submandibular gland (3). The lacrimal and parotid glands were very close to each other.…”
mentioning
confidence: 84%